The adsorption of quinizarin on boron-doped diamond. - Dimov, I; Batchelor-McAuley, C; Aldous, L; Compton, R (2012)
The voltammetric response of the quinone species 'quinizarin' (QZ) and its electrocatalytic reduction of oxygen are studied at a boron doped diamond electrode (BDD). It is demonstrated that, contrary to the widespread belief that adsorption of organic molecules on BDD is minimal, not only does QZ readily adsorb to the electrodes surface but this adsorption is also influenced at low surface coverages by the pre-exposure of the electrode to organic solvents. Furthermore, the nature of this adsorbed QZ species is investigated and a potential dependent phase transition is observed. This is to the authors knowledge the first system to exhibit a phase transition of an adsorbed species on a boron doped diamond surface. At low scan rates the system is found to oscillate; these oscillations are ascribed to the presence of a 'negative differential resistance'.